In defense of a liberal education [compact disc, unabridged] - Zakaria, Fareed (Audioworks, Simon & Schuster Audio, 2015)
Argues for the virtues of a liberal arts education even as cultural trends are moving toward skill-based education, citing such benefits as the ability to write, express oneself, think critically, be creative, communicate, and learn as the indispensable gifts of liberal education.